PENGARUH GAYA KEPEMIMPINAN ISLAM DALAM MENINGKATKAN ETOS KERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA IV UNIT KEBUN TIMUR - Sudirman Sudirman (IAIN Batusangkar, 2019)
This research is aimed to examine and find out empirical evidence of the Islamic leadership style on employee work ethic. Sampled used in this research are employees at during afdelling I-VI. The data are collected using purposive sampling method. The analysis of this research employs simple linear regression. Result show that Islamic Leadership Style have significant and positive effect on employee work ethic with the magnitude of the influence of 9% and the contribution of the variable Islamic Leadership Style worth 27.3%.